2008
DOI: 10.1111/j.1745-4565.2008.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Microbiological Quality of the Bonab Kebabs Sold in Tabriz Market

Abstract: The objective of this research was to determine chemical composition and microbiological quality of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Regardless of mince stew, bacterial contamination was not detected in other stews, which could be related to the long time of cooking and high temperature (6,8,10); This finding was also previously observed in another study performed by Tavakoli et al, in 2009 to evaluate the bacterial, chemical and organoleptic quality of cooked food with traditional and modern equipment. They stated that high cooking temperature is effective in reducing the contamination level; however, the quantity of vitamin B1 and B2 in addition to the organoleptic characteristics may decrease as a result of high cooking temperature (11).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Regardless of mince stew, bacterial contamination was not detected in other stews, which could be related to the long time of cooking and high temperature (6,8,10); This finding was also previously observed in another study performed by Tavakoli et al, in 2009 to evaluate the bacterial, chemical and organoleptic quality of cooked food with traditional and modern equipment. They stated that high cooking temperature is effective in reducing the contamination level; however, the quantity of vitamin B1 and B2 in addition to the organoleptic characteristics may decrease as a result of high cooking temperature (11).…”
Section: Discussionsupporting
confidence: 79%
“…Findings of the performed study by Nemati et al on kebab have shown that the total bacterial and coliform counts were 3.22 × 10 3 CFU/g and 1.69 × 10 3 CFU/g, respectively which is higher than our results. Insufficient heat and secondary contamination after cooking, inappropriate preparation and contaminated masher could be effective in food contamination (10).…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the foods that have been contaminated and temperature abused or spoilt [3]. In the previous study [4], stated that the contamination can also cause by insufficient heat during cooking process. However, high load of TPC in meat-based preparations might even be due to the existence of spoilage bacteria which is able to grow on a non-selective plate count agar medium [5].…”
Section: Resultsmentioning
confidence: 97%
“…These results are similar to ours. However, some other studies showed a greater decreasing ratio in microbial load by cooking (15,(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 93%